1997
DOI: 10.1007/bf00941803
|View full text |Cite
|
Sign up to set email alerts
|

One-point measurement of the peak-to-peak pulsatility index as an indicator for evaluation of infrainguinal bypass procedures

Abstract: While duplex scanning has been advocated as the most accurate modality for postoperative graft surveillance, it is time-consuming for evaluating the entire graft. The aim of the present study was to determine which parameter predicts graft failure most simply and precisely, by examining 62 men and 1 woman who collectively underwent 71 infrainguinal arterial bypasses. A total of 212 scannings were obtained using a duplex scanner, and the peak systolic velocity (PSV), PSV ratio, and peak-to-peak pulsatility inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In this series, PPI criteria revealed excellent sensitivity and sufficient specificity as a screening test if the cutoff level was 7.0, which we also advocated in our previous study. 8 Several clinical series have shown that the PPI value exhibited sufficient sensitivity to predict significant proximal stenosis if no additional distal lesions, and hence no additional positive reflection sites, existed. 9-11 Johnston et al 10 assessed four methods, namely, pulsatility index, height-width index, path length index, and Laplace transform function index.…”
Section: Discussionmentioning
confidence: 99%
“…In this series, PPI criteria revealed excellent sensitivity and sufficient specificity as a screening test if the cutoff level was 7.0, which we also advocated in our previous study. 8 Several clinical series have shown that the PPI value exhibited sufficient sensitivity to predict significant proximal stenosis if no additional distal lesions, and hence no additional positive reflection sites, existed. 9-11 Johnston et al 10 assessed four methods, namely, pulsatility index, height-width index, path length index, and Laplace transform function index.…”
Section: Discussionmentioning
confidence: 99%